Struktur, Komposisi serta Potensi Tumbuhan Bawah sebagai Tumbuhan Obat di Hutan Heterogen di Desa Cikakak Kecamatan Wangon Kabupaten Banyumas - Sulistyani Sulistyani; Erie Kolya Nasution; Hexa Apriliana Hidayah (Fakultas Biologi | Universitas Jenderal Soedirman, 2012)
A research entitled “The structure, Composition and Potency of Ground Vegetation as Medical Plants in Heterogenous Forest at Cikakak Village Wangon Subdistrict banyumas Regency” aims to find out the structure and composition of ground vegetation species and ground vegetation that have a potency of medicalplants. Material and tools usud in this reseach were ground vegetation is sublimat, GPS, altimeter, thermohygrometer, soiltester, luxmeter, plastic bags, rollmeter, sasak. The research were used survei methode and square plots quadrate methode used a sampling method. The result of the observation showed that ground vegetation composition of heterogenous forets at Cikakak village Wangon subdistrict Banyumas regency was builled from 72 species belonging to 33 families and order from the most to the least abundance habitus were follow herb 49 species ,shrub 11 species, seedling 8 species, and liana 3 species. The result of the reseach ground vegetation potency as big enough medical plants ist 65,27 %.